Utang Dalam Negeri dan Pertumbuhan Ekonomi Sebuah Analisis Kausalitas: Bukti Empiris Indonesia - Suhendra, Noval; Hatmawan, Aglis Andhita; Ningsih, Lia Sulistia; Hartini, Hartini; Shifa, Mutiara; Ariani, Dian; Tanjung, Indra Ismayudi (Universitas Teuku Umar, 2024)
This research aims to analyze the impact of domestic debt on economic growth in Indonesia with a causal approach. The research data used is quarterly for the period 2004-2022. Meanwhile, the main variables analyzed in this research are projected economic growth through GDP, domestic debt, and several control variables such as exports, imports, and interest rates which are then analyzed using VECM. Based on the VECM estimation results, it is found that domestic debt has a negative and significant influence on economic growth in both the short and long term. On the other hand, economic growth has no significant influence on domestic debt. If we look at the percentage strength, in the short term, when a domestic debt shock occurs, it will fluctuate economic growth by 7 percent, while in the long term, the domestic debt shock will have an impact on economic growth of 24 percent. The results of this research can be a recommendation to the government or non-government institutions that in seeking additional financing these institutions can also make domestic loans, although the desired debt amount must be adjusted so as not to harm Indonesia's economic conditions.